Productivity of winter maize as affected by varieties and fertilizer levels - Bishnu Hari Adhikary; Bandhu Raj Baral; Jiban Shrestha (International Journal of Applied Biology, 2020)
Grain yield production of maize is greatly affected by varieties and fertilizer levels. This study was conducted to determine the effects of different rates of fertilizers (nitrogen, phosphorus, potassium fertilizers and farmyard manures) on grain yield and yield attributing traits of different maize varieties during winter seasons of 2009/10 and 2010/011 at the research farm of National Maize Research Program, Rampur, Chitwan, Nepal. Six levels of fertilizers [Control (Zero fertilizer), FYM @ 10 t/ha, FYM@ 10 t/ha plus 60:30 20 kg NPK/ha, FYM@ 10 t/ha plus 120: 60: 40 kg NPK/ha, FYM@ 10 t/ha plus 180: 90: 60 kg NPK/ha, and 120: 60: 40 kg NPK/ha] and four maize varieties (Rampur Composite, Manakamana-4, Across9942 × Across 9944 and S99TLYQ-B) were evaluated in randomized complete block design with three replications. The results showed that grain yield was non-significant for maize genotypes but the fertilizers levels were highly significant for grain yield. Rampur Composite produced the highest grain yield (5195 kg/ha), followed by Manakamana-4 (5074 kg/ha), Across9942 × Across9944 (5052 kg/ha) and S99TLYQ-B (4789 kg/ha) with the application of NPK 180: 90: 60 kg/ha plus FYM 10 t/ha. This information is useful in generating suitable fertilization packages for obtaining higher grain yield of maize varieties.